Players` physical performance decreased after two-thirds of the season: Results of 3 consecutive seasons in the German first Bundesliga - Chmura, P.; Konefal, M.; Wong, D. P.; Figueiredo, A.; Kowalczuk, E.; Rokita, A.; Chmura, J.; Andrzejewski, M. (International Journal of Environmental Research and Public Health, 2019)
The study aimed to: (1) investigate physical and technical performance among players during six consecutive phases of a competitive season, (2) determine if levels of match running and technical performance between the 1st and 6th phases of a season can be maintained, (3) and determine which phase features the lowest and highest values for variables assessed. Seventy out of 556 outfield players who played at least 80% of the matches in each phase of the Bundesliga seasons were analysed. Each season was divided into 6 phases: phase 1 (matches 1-6), phase 2 (7-11), phase 3 (12-17), phase 4 (18-23), phase 5 (24-28) and phase 6 (29-34). Thirteen variables were selected to quantify the physical and technical activity of players. Our results showed that by reducing the distances covered at intensities below 11 km·h-1, players were able to cover greater distances at intensities in the range of 11-13.99 and 21-23.99 km·h-1 in subsequent phases of a season. Players` capacity to maintain match running and technical performance between the first and sixth phases of the season has been demonstrated, though the 4th phase of the season showed a breakthrough point as regards the maintenance of exercise capacity among players participating in the Bundesliga.